Integration of AI-2 Based Cell-Cell Signaling with Metabolic Cues in Escherichia coli - Mitra, A.; Herren, Christopher D.; Patel, I. R.; Coleman, A.; Mukhopadhyay, S. (My University, 2017)
The quorum sensing molecule Autoinducer-2 (AI-2) is generated as a byproduct of activated methyl cycle by the action of LuxS in Escherichia coli. AI-2 is synthesized, released and later internalized in a cell-density dependent manner. Here, by mutational analysis of the genes, uvrY and csrA, we describe a regulatory circuit of accumulation and uptake of AI-2. We constructed a single-copy chromosomal luxS-lacZ fusion in a luxS (+) merodiploid strain and evaluated its relative expression in uvrY and csrA mutants. At the entry of stationary phase, the expression of the fusion and AI-2 accumulation was positively regulated by uvrY and negatively regulated by csrA respectively. A deletion of csrA altered message stability of the luxS transcript and CsrA protein exhibited weak binding to 5' luxS regulatory region. DNA protein interaction and chromatin immunoprecipitation analysis confirmed direct interaction of UvrY with the luxS promoter. Additionally, reduced expression of the fusion in hfq deletion mutant suggested involvement of small RNA interactions in luxS regulation. In contrast, the expression of lsrA operon involved in AI-2 uptake, is negatively regulated by uvrY and positively by csrA in a cell-density dependent manner. The dual role of csrA in AI-2 synthesis and uptake suggested a regulatory crosstalk of cell signaling with carbon regulation in Escherichia coli. We found that the cAMP-CRP mediated catabolite repression of luxS expression was uvrY dependent. This study suggests that luxS expression is complex and regulated at the level of transcription and translation. The multifactorial regulation supports the notion that cell-cell communication requires interaction and integration of multiple metabolic signals.
Citation: Mitra, A., Herren, C. D., Patel, I. R., Coleman, A., & Mukhopadhyay, S. (2016). Integration of AI-2 Based Cell-Cell Signaling with Metabolic Cues in Escherichia coli. Plos One, 11(6), 19. doi:10.1371/journal.pone.0157532
Keywords: Virulence Gene-Expression; Salmonella-Typhimurium; Response Regulator; Biofilm Formation; Vibrio-Cholerae; Global Control